Legal Protection and Fulfillment of Children's Right to Education Through the Foster Sister Program in a Welfare Perspective - Shodiqin, Muhammad; Zakki, Muhammad; Farid, Mohamad; Evendi, Wakid; Aliyah, Nelud Darajaatul (Indonesian Journal of Research and Service Studies, 2024)
The deterioration of the family economy is the main problem in fulfilling children's rights in the world of education, thus giving birth to a vulnerable community which results in a large number of school dropouts (ATS). In addition, as a result of weak family understanding, also supported by economic problems against the fulfillment of the child's right to education, causing loss of access in providing children's education services that affect the child's enthusiasm and ethos to learn, especially in orphans who are a vulnerable group that should receive handling and rescue efforts, because it causes the right to education and the right to children's welfare neglected so that the role and involvement of the community is needed through cooperation and partnership models. Community Service Activities (PKM) are carried out with a qualitative approach the Asset-Based Community Development (ABCD) method is a sustainable empowerment method based on the assets, strengths, and potentials of the Community by looking at the aspects of capacity, associations, and existing institutions or institutions by mobilizing the capabilities of all resources, skills, and community experience as the main foothold to improve the quality of life in various aspects in Community. Community Service through this model is a solution to solving problems in society related to the fulfillment of the right to education and welfare for children which is part of the form of community involvement in helping the Government which is trying to make efforts to build social welfare and overcome economic downturns, the widespread number of children dropping out of school and cutting other social problems in the future as a result of low levels of education in vulnerable communities, this is so that social justice can be realized for all Indonesian people.